A polysulfone-ZrO2 composite membrane material, preparation method and application

By adding organosiloxane coupling agent to the polysulfone-ZrO2 composite film material, modifying the surface of ZrO2 and forming a -Si-O-Zr bond, the problem of poor compatibility between polysulfone and ZrO2 is solved, and high compatibility is achieved , excellent mechanical properties, good hydroxide conductivity and gas barrier properties, suitable for alkaline electrolytic devices.

CN115181996BActive Publication Date: 2025-02-21NIGBO SINO TECH HYDROGEN MEMBRANE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210867397.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-21
Publication Date
2025-02-21
Estimated Expiration
2042-07-21

AI Technical Summary

Technical Problem

In the existing alkaline electrolytic devices, the polysulfone and ZrO2 interface compatibility are poor, resulting in high membrane brittleness, poor mechanical properties, and poor hydroxide conductivity and gas barrier properties.

Method used

Polysulfone-ZrO2 composite film material is prepared by adding organosiloxane coupling agent. The silicone group modifies the ZrO2 surface to form a -Si-O-Zr bond, improves interface compatibility, thereby improving mechanical properties and hydrogen Oxygen conductivity.

Benefits of technology

It achieves high compatibility, excellent mechanical properties, good hydroxide conductivity and gas barrier properties, and is suitable for alkaline electrolytic devices, improving the stability and efficiency of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115181996B_ABST
    Figure CN115181996B_ABST
Patent Text Reader

Abstract

The present invention discloses a polysulfone-ZrO2 composite membrane material, a preparation method and an application. By adding one or more organic siloxane coupling agents, the siloxane group of the coupling agent modifies the ZrO2 surface, the organic part is bonded to the polysulfone, and a -Si-O-Zr bond is formed between the two organic and inorganic components of polysulfone and ZrO2 to improve the interfacial compatibility, thereby improving the mechanical properties of the composite membrane material without sacrificing hydrophilicity. The method is simple and efficient to operate. The prepared polysulfone-ZrO2 composite membrane material has high compatibility, uniformly distributed porous structure, excellent mechanical properties, high gas barrier properties, good stability and high hydroxide conductivity, and has good application prospects in alkaline water electrolysis devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polysulfone-ZrO2 composite membrane material, a preparation method and application thereof, and belongs to the field of alkaline water electrolysis membrane materials. Background Art

[0002] The development of clean and efficient renewable energy is an inevitable trend in future energy transformation. Hydrogen energy, as a green and pollution-free energy carrier, can achieve efficient conversion of hydrogen energy and electrical energy through water electrolysis technology. Among them, alkaline water electrolysis (AWE) is a recognized mature and reliable water electrolysis system. Because in alkaline media, it can use non-precious metals such as iron and nickel as electrode materials, overcoming the expensive equipment and resource constraints caused by the use of precious metal catalysts in proton exchange membrane water electrolysis (PEMWE) hydrogen production, and avoiding the use of expensive titanium-based components (International Journal of Energy Research, 2020, 44 (3): 1875-1885). However, the electrolysis efficiency of alkaline electrolyzers is low. As a key material for alkaline water electrolysis (AWE), it is particularly important to develop a good, stable and excellent isolation membrane.

[0003] Recently, it has been found that alkaline electrolyzers using anion exchange membranes (AEMs) can achieve over 2 A / cm 2AEMs have a high current density (Journal of Membrane Science.2019,581,139-149) and a high electrolysis efficiency comparable to PEMWE (Journal of The Electrochemical Society.2017,164,F1187-F1195), but during performance testing, CO2 pollution in the air and polymer degradation are still the main problems of AEMs (Journal of Membrane Science.2014,464,61-71). Similarly, although the ion solvation membrane used for alkaline water electrolysis has excellent gas barrier properties, its hydroxide conductivity is heavily dependent on high-concentration alkaline electrolytes, and at high temperatures, its alkali resistance stability is still to be improved. Therefore, most commercial alkaline water electrolyzers still use porous diaphragms with good alkali resistance when circulating electrolytes. A porous diaphragm is an isolating material that relies solely on electrolytes to establish a permeation path through a porous structure. In the past, commercial AWEs mostly used asbestos and polyphenylene sulfide (PPS) as separation membranes. Asbestos is no longer used due to its carcinogenic properties and instability at high temperatures. The bubble point pressure of PPS fabric is below 0.02 bar and is not suitable for pressurized AWE. Therefore, a class of composite membranes has emerged, whose membrane matrix is ​​made of stable inert polymers and is usually filled and supported by hydrophilic inorganic materials. Polyamino acids were first developed for alkaline water electrolyzers due to their high alkali resistance. Potassium titanate, titanium dioxide, sintered nickel plates and zirconium oxide as separation materials show good stability in electrochemical systems (Polymers.2020,12,2821). The current advanced commercial composite membrane Zirfon PERL is composed of 85wt% ZrO2 nanoparticles and 15wt% polysulfone (PSF), which is very stable in 80°C, 30wt% KOH solution. However, due to the poor surface compatibility of polysulfone and hydrophilic zirconium oxide particles, the organic polymer-inorganic filler interaction is weak, resulting in large film brittleness and poor mechanical properties. PA Jacobs found that the surface characteristics of inorganic fillers greatly affect the performance of composite films (The Journal of Physical Chemistry B.2006,110,7425-7430). Zhang et al. prepared functionalized TiO2 submicrospheres by using surfactants. The SO3H group strengthened the interaction between the inorganic filler and the polymer matrix and improved the compatibility of the interface, but the functionalization process was cumbersome (Electrochimica Acta 2015,177,128-136).AF Ismail used a silane coupling agent (AAPTS) containing NH2 functional groups to modify the surface of synthesized TiO2 nanoparticles to improve their distribution in polysulfone, thereby preparing a new type of nano-ultrafiltration composite membrane (Nanotechnology 2016, 27, 415706). Lee et al. reported a porous composite diaphragm of zirconium dioxide / polysulfone. By controlling the preparation factors such as coagulation bath temperature, polyvinyl pyrrolidone content and diaphragm thickness, the morphology, structure and electrochemical properties of the zirconium dioxide / polysulfone porous membrane can be effectively regulated (Journal of Membrane Science, 2020, 616: 118541). Cho et al. used cellulose nanocrystals as organic blends to prepare a polysulfone-ZrO2 composite membrane with good mechanical properties and excellent hydrophilicity (Chemical Engineering Journal, 2022, 428: 131149). However, the compatibility problem at the interface between polysulfone and ZrO2 has not been well solved. Therefore, the development of a simple, efficient, highly compatible, stable, low ohmic internal resistance and high gas barrier porous membrane is of great significance for the commercial application of AWE. Summary of the invention

[0004] The purpose of the present invention is to provide a polysulfone-ZrO2 composite membrane material, a preparation method and an application thereof. The polysulfone-ZrO2 composite membrane material has high compatibility, excellent mechanical properties, high gas barrier properties and high hydroxide conductivity. The application thereof is an application in an alkaline water electrolysis device.

[0005] In the present invention, the polysulfone-ZrO2 composite membrane material is a composite porous diaphragm.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] The present invention provides a method for preparing a polysulfone-ZrO2 composite membrane material, which is a method for preparing a polysulfone-ZrO2 composite membrane material by adding an organic siloxane coupling agent. The siloxane group of the coupling agent modifies the ZrO2 surface, the organic part bonds with the polysulfone, and a -Si-O-Zr bond is formed between the two organic-inorganic components of the polysulfone and ZrO2 to improve the interface compatibility, thereby improving the mechanical properties of the composite membrane material without sacrificing hydrophilicity.

[0008] A polysulfone-ZrO2 composite membrane material, the composite membrane material is made of raw materials including ① ZrO2, ② polysulfone, and ③ one or more organic siloxane coupling agents; the ratio of ZrO2 to polysulfone is represented by A:B, wherein A represents the mass proportion of polysulfone, B represents the mass proportion of ZrO2, A is 0.05-0.45, B is 0.65-0.95, A+B=1.0 (if A is lower than 0.05, the formed composite membrane is brittle and has poor flexibility and cannot be used normally; if A is higher than 0.45, the composite membrane will have poor hydrophilicity and low hydroxyl conduction level). At the same time, the mass (x) of the one or more coupling agents to the mass (y) of ZrO2 is 0.01-1 (i.e. x / y=0.01-1).

[0009] The general structural characteristics of the organosiloxane coupling agent are as follows:

[0010]

[0011] R is any of the following groups:

[0012]

[0013] Further, A is 0.05-0.45. For example, A is 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40 or 0.45.

[0014] Furthermore, B is 0.65 to 0.95. For example, B is 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 or 0.95.

[0015] Furthermore, the ratio of the mass x of the organosiloxane coupling agent to the mass y of ZrO2, that is, x / y is 0.01, 0.05, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90 or 1; preferably, x / y is 0.05, 0.10, 0.20 or 0.3;

[0016] The method for preparing the polysulfone-ZrO2 composite membrane material of the present invention comprises the following steps:

[0017] (1) At room temperature, ① ZrO2 and ③ one or more organosiloxane coupling agents are first dispersed in an organic solvent to obtain a mixed solution, the mixed solution is further ground and dispersed for 0.5-1h, then stirred at 80-120°C for 0.5-2h, and then polysulfone is added in batches and stirred for 2-6h, and the solid content of the final casting solution is controlled at 50-70wt%.

[0018] (2) Next, the obtained casting solution is coated on a glass plate, pre-evaporated at room temperature for 5-300 seconds, and then slowly immersed in one or more mixed non-solvents at -25-30°C for 5-30 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion.

[0019] (3) Soaking the membrane obtained in the above step in deionized water at 50-100° C. for 24-48 hours to fully remove the residual solvent in the membrane, and finally preparing a polysulfone-ZrO2 composite porous membrane material. The polysulfone-ZrO2 composite membrane material has a pore size of 0.05-150 nm, a porosity of 1-200%, and a thickness of 80-500 μm.

[0020] Furthermore, the organic solvent in step (1) is N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or tetramethyl urea (TMU) or the like.

[0021] Furthermore, the non-solvent described in step (2) is one or a mixed solvent of two or more selected from the group consisting of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol and tert-butanol.

[0022] The application of the polysulfone-ZrO2 composite membrane material of the present invention in an alkaline water electrolysis device comprises the following steps:

[0023] (1) Preparation of membrane electrode assembly for water electrolysis device. Pure nickel mesh foam was used for both cathode and anode. The pure nickel mesh foam was hot pressed at 80-120°C for 0.5-10 minutes in a hot press and then taken out and compressed to a thickness of 150-200 μm. Then, the polysulfone-ZrO2 composite membrane material was sandwiched between two nickel mesh foam electrodes to obtain a membrane electrode assembly with an effective area of ​​4 cm 2 .

[0024] (2) The membrane electrode assembly was sandwiched between the cathode and the anode to assemble the water electrolysis device. The electrochemical test was carried out while the anode and cathode were immersed in electrolyte. Polarization curves were obtained by measuring the cell voltage at different current densities under the conditions of 1-10M KOH and 20-100°C, and the polarization curves were obtained under the conditions of 20-100°C, 50-500mA·cm -2 The durability is evaluated under constant temperature and constant current conditions.

[0025] According to the application of the polysulfone-ZrO2 composite membrane material in an alkaline water electrolysis device, it is characterized in that the electrolyte in the alkaline water electrolysis device is one or more of potassium hydroxide, potassium carbonate, potassium bicarbonate, sodium hydroxide, sodium carbonate, and sodium bicarbonate.

[0026] The beneficial results of the present invention are:

[0027] (1) The present invention proposes a method for preparing a highly compatible polysulfone-ZrO2 composite membrane material by adding an organic siloxane coupling agent, which is simple and efficient to operate.

[0028] (2) The prepared polysulfone-ZrO2 composite membrane material has high compatibility and excellent mechanical properties, with a tensile strength of 50-70MPa and an elongation at break of 8-15%;

[0029] (3) The composite membrane material prepared by phase inversion in the present invention has good compatibility, the formed pore size is relatively uniform, the conductivity of hydroxide is high, and the gas barrier property is strong. Such a membrane has a very good application prospect in alkaline water electrolysis devices;

[0030] (4) The polysulfone-ZrO2 composite membrane material is used in an alkaline water electrolysis device and has excellent water electrolysis performance and durable stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The SEM images of the polysulfone-ZrO2 composite membrane materials prepared in Example 1 and the comparative example;

[0032] Figure 2 Polarization curves of the polysulfone-ZrO2 composite membrane materials prepared in Examples 1, 2, 6, 8, 9 and the comparative example at 6M and 80°C in an alkaline water electrolysis device;

[0033] Figure 3 Example 6 at 80°C, 6M KOH, 500mA / cm 2 Durability stability test under . DETAILED DESCRIPTION

[0034] The technical solution of the present invention is described in detail below through specific embodiments, but it should be clearly stated that these embodiments are for illustration and are not to be construed as limiting the scope of the present invention.

[0035] Some of the raw materials used in the following examples of the present invention come from:

[0036] Polysulfone (Sigma-Aldrich, 428302, M w =50000-500000)

[0037] ZrO2 (Sigma-Aldrich, 230693, particle size 20-2000nm)

[0038] Example 1

[0039] (1) At room temperature, 85 g ZrO2 and 8.5 g n-octyltriethoxysilane (Annage Chemical, E010455) (x / y=0.1, x refers to the mass of n-octyltriethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5 h, and then stirred at 120 ° C for 2 h, and then 15 g polysulfone was added in batches and stirred at high speed for 3 h. Finally, the solid content of the casting solution was controlled at 60 wt%.

[0040] (2) Next, the obtained casting solution was coated on a clean glass plate, pre-evaporated at room temperature for 10 seconds, and then slowly immersed in isopropanol at 0°C for 5 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion.

[0041] (3) The membrane obtained in the above steps was immersed in deionized water at 80°C for 24 h to fully remove the residual solvent in the membrane. The polysulfone-ZrO2 composite membrane material was finally prepared. The membrane thickness was 150 μm, the compatibility was good, and the mechanical properties were excellent (elastic modulus was 927.05 MPa; elongation at break was 6.87%; tensile strength was 51.32 MPa), and the membrane surface resistance was 0.28 mΩ×cm 2 .

[0042] The steps for applying the prepared polysulfone-ZrO2 composite membrane material in an alkaline water electrolysis device are as follows:

[0043] (1) Preparation of membrane electrode assembly for alkaline water electrolysis device. Pure nickel mesh foam (Suzhou Shengerno Technology, thickness 500 μm) was selected for both anode and cathode. The pure nickel mesh foam (2 cm × 2 cm) was placed in a hot press and hot-pressed at 80°C for 5 minutes. After that, it was taken out and compressed to a thickness of 180 μm. Then, the prepared polysulfone-ZrO2 composite membrane material was sandwiched between two nickel mesh foam electrodes to obtain a membrane electrode assembly with an effective area of ​​4 cm 2 .

[0044] (2) The alkaline water electrolysis device was assembled by sandwiching the membrane electrode assembly between the cathode and the anode. The electrochemical test was carried out while the membrane electrode was immersed in the anode and cathode electrolytes. The initial performance was 500 mA cm at 6 M KOH and 80 °C. -2 -1.90V, and at 80℃, 200mA·cm -2 The durability was evaluated under a constant current.

[0045] Example 2

[0046] At room temperature, 85g ZrO2 and 8.5g allyl triethoxysilane (Annaiji Chemical, D033314) (x / y=0.1, x refers to the mass of allyl triethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 15g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 60wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 200μm.

[0047] Example 3

[0048] At room temperature, 85g ZrO2 and 17g allyl triethoxysilane (Annaiji Chemical, D033314) (x / y=0.2, x refers to the mass of allyl triethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 15g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 60wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 150μm.

[0049] Example 4

[0050] At room temperature, 75g ZrO2 and 15g allyl triethoxysilane (Annaiji Chemical, D033314) (x / y=0.2, x refers to the mass of allyl triethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 25g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 60wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 120μm.

[0051] Example 5

[0052] At room temperature, 65g ZrO2 and 13g allyl triethoxysilane (Annaiji Chemical, D033314) (x / y=0.2, x refers to the mass of allyl triethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 35g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 60wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 150μm.

[0053] Example 6

[0054] At room temperature, 85g ZrO2 and 25.5g phenyltriethoxysilane (Annaiji Chemical, W310041) (x / y=0.3, x refers to the mass of phenyltriethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 15g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 70wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 200μm.

[0055] Example 7

[0056] At room temperature, 85g ZrO2 and 17g phenyltriethoxysilane (Annaiji Chemical, W310041) (x / y=0.2, x refers to the mass of phenyltriethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 15g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 60wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 170μm.

[0057] Example 8

[0058] At room temperature, 95g ZrO2 and 19g (3-aminopropyl) triethoxysilane (Annaiji Chemical, E080931) (x / y=0.2, x refers to the mass of (3-aminopropyl) triethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 5g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 65wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 210μm.

[0059] Example 9

[0060] At room temperature, 80 g ZrO2 and 4 g benzyltriethoxysilane (Annaiji Chemical, M0100498) (x / y=0.05, x refers to the mass of benzyltriethoxysilane, y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 0.5 h, then stirred at 120 ° C for 2 h, and then 20 g polysulfone was added in batches for high-speed stirring for 3 h, and the solid content of the final casting solution was controlled at 75 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 240 μm.

[0061] Example 10

[0062] At room temperature, 80g ZrO2, 2g benzyltriethoxysilane (Annaiji Chemical, M0100498), and 2g hexyltriethoxysilane (Annaiji Chemical, E080836) (x / y=0.05, x refers to the mass of benzyltriethoxysilane and hexyltriethoxysilane, and y refers to the mass of ZrO2) were first dispersed in N,N'-dimethylformamide (DMF), and the mixed solution was further ground and dispersed by a ball mill for 0.5h, and then stirred at 120°C for 2h, and then 20g polysulfone was added in batches for high-speed stirring for 3h, and the solid content of the final casting solution was controlled at 75wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 220μm.

[0063] Embodiment 11

[0064] The same as Example 1, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane material: the obtained casting solution is scraped on a clean glass plate, pre-evaporated at room temperature for 30 seconds, and then slowly immersed in methanol at -10°C for 10 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion. The remaining experimental steps and application steps are the same as Example 1, and the obtained composite membrane material has a film thickness of 180 μm.

[0065] Example 12

[0066] The same as Example 1, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane material: the obtained casting solution is scraped on a clean glass plate, pre-evaporated at room temperature for 60 seconds, and then slowly immersed in methanol at -10°C for 10 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion. The remaining experimental steps and application steps are the same as Example 1, and the obtained composite membrane material has a film thickness of 200 μm.

[0067] Example 13

[0068] The same as Example 9, except that in the specific step (2) of preparing the polysulfone-ZrO2 composite membrane material: the obtained casting solution is scraped on a clean glass plate, pre-evaporated at room temperature for 10 seconds, and then slowly immersed in a mixed solution of ethanol and water (ethanol: water volume ratio = 1:1) at -15°C for 15 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase conversion. The remaining experimental steps and application steps are the same as Example 1, and the obtained composite membrane material has a film thickness of 220 μm.

[0069] Embodiment 14

[0070] The same as Example 9, except that in the specific step (1) of preparing the polysulfone-ZrO2 composite membrane material: at room temperature, firstly, 80g ZrO2 and 4g benzyltriethoxysilane (Annaiji Chemical, M0100498) (x / y=0.05, x refers to the mass of benzyltriethoxysilane, y refers to the mass of ZrO2) are dispersed in N-methylpyrrolidone (NMP), the mixed solution is further ground and dispersed by a ball mill for 0.5h, then stirred at 120°C for 2h, and then 20g polysulfone is added in batches for high-speed stirring for 3h, and the solid content of the final casting solution is controlled at 75wt%. The remaining experimental steps and application steps are the same as those in Example 1, and the obtained composite membrane material has a film thickness of 160μm.

[0071] Comparative Example

[0072] In this example, a polysulfone-ZrO2 composite membrane material was prepared without adding an organic siloxane coupling agent as a comparative example: at room temperature, 85 g of ZrO2 was first dispersed in N,N'-dimethylformamide (DMF), the mixed solution was further ground and dispersed by a ball mill for 0.5 h, and then stirred at 120°C for 2 h, and then 15 g of polysulfone was added in batches for high-speed stirring for 3 h, and the solid content of the final casting solution was controlled at 60 wt%. The remaining experimental steps and application steps were the same as in Example 1, and the obtained composite membrane material had a film thickness of 270 μm.

[0073] Figure 1 The following are SEM images of the polysulfone-ZrO2 composite membrane materials prepared in Example 1 and the comparative example. Figure 1 (a) is the SEM image of the upper surface of the comparative composite membrane, which shows that polysulfone has poor compatibility with ZrO2, uneven dispersion, and ZrO2 agglomerates; Figure 1 (b) is a SEM image of the upper surface of the composite membrane of Example 1, from which it can be seen that polysulfone and ZrO2 have good compatibility, are evenly distributed, and are tightly bonded.

[0074] Table 1 shows the mechanical properties and membrane surface resistance performance parameters of the polysulfone-ZrO2 composite membrane materials prepared in all embodiments and comparative examples. Specifically, Table 1 shows the mechanical properties comparison of the polysulfone-ZrO2 composite membrane materials prepared in all embodiments and comparative examples; Table 1 shows the membrane surface resistance comparison of the polysulfone-ZrO2 composite membrane materials prepared in all embodiments and comparative examples at 6M KOH and room temperature.

[0075] Table 1

[0076]

[0077] It can be found from Table 1 that compared with not adding siloxane coupling agent, after adding siloxane coupling agent, the elongation at break and tensile strength of the composite film are improved to varying degrees, and the film surface resistance can also be maintained unchanged or reduced.

[0078] Figure 2 The polarization curves of the polysulfone-ZrO2 composite membrane materials prepared in Examples 1, 2, 6, 8, 9 and the comparative example on the alkaline water electrolysis device are shown in the figure. As can be seen from the figure, compared with the comparative example, the water electrolysis performance of the embodiments has been improved to a certain extent, among which the polysulfone-ZrO2 composite membrane material prepared in Example 6 has the best performance, and the polysulfone-ZrO2 composite membrane material prepared in the comparative example has the best performance at 500mA / cm 2 The voltage is as high as 2.02V. The polysulfone-ZrO2 composite membrane material prepared in Example 6 is 500mA / cm 2 The lower voltage is only 1.80V.

[0079] Figure 3The polysulfone-ZrO2 composite membrane material prepared in Example 6 was heated at 80°C, 6M KOH, 500mA / cm 2 As can be seen from the figure, the stability of the polysulfone-ZrO2 composite membrane material prepared in Example 6 in the alkaline water electrolysis device is higher than that of the comparative example. After 265 hours, the voltage slowly rises from 1.802V to 1.82V, while the voltage of the comparative example rises rapidly from 2.05V to 2.15V after 120 hours.

[0080] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A polysulfone-ZrO2 composite membrane material, characterized in that: The composite membrane material is made of raw materials including ① ZrO2, ② polysulfone, and ③ one or more organic siloxane coupling agents; the ratio of ZrO2 to polysulfone is represented by A:B, wherein A represents the mass proportion of polysulfone, B represents the mass proportion of ZrO2, A is 0.05-0.45, B is 0.65-0.95, and A+B=1.0; the ratio of the mass x of the organic siloxane coupling agent to the mass y of ZrO2 is 0.01-1; The general structural formula of the organosiloxane coupling agent is as follows: R is any one of the groups represented by formula (a), (b), (c), (d), (e), (f), (g), (h), (I) and (j), The preparation method of the composite membrane material comprises the following steps: (1) At room temperature, ZrO2 and one or more organosiloxane coupling agents are first dispersed in an organic solvent to obtain a mixed solution, the mixed solution is further ground and dispersed, and then stirred at 80-120° C. for 0.5-2 h, and then polysulfone is added in batches and stirred for 2-6 h, and the solid content of the final casting solution is controlled at 50-70 wt %; (2) Next, the obtained casting solution is coated on a glass plate by knife coating, pre-evaporated at room temperature for 5-300 seconds, and then immersed in one or more mixed non-solvents at -25-30°C for 5-30 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion; (3) Soaking the membrane obtained in the above step in deionized water at 50-100° C. for 24-48 hours to remove the residual solvent in the membrane, and finally preparing a polysulfone-ZrO2 composite membrane material.

2. The composite membrane material according to claim 1, characterized in that: The ratio of the mass x of the organic siloxane coupling agent to the mass y of ZrO2 is 0.05 to 0.

3.

3. The composite membrane material according to claim 1, characterized in that: The siloxane group of the organosiloxane coupling agent modifies the surface of ZrO2, and the organic part of the organosiloxane coupling agent bonds with polysulfone to form a -Si-O-Zr bond between the two organic-inorganic components of polysulfone and ZrO2; The polysulfone-ZrO2 composite membrane material has a pore size of 0.05-150 nm, a porosity of 1-200%, and a thickness of 80-500 μm.

4. A method for preparing the polysulfone-ZrO2 composite membrane material according to any one of claims 1 to 3, characterized in that: The steps include: (1) At room temperature, ZrO2 and one or more organosiloxane coupling agents are first dispersed in an organic solvent to obtain a mixed solution, the mixed solution is further ground and dispersed, and then stirred at 80-120° C. for 0.5-2 h, and then polysulfone is added in batches and stirred for 2-6 h, and the solid content of the final casting solution is controlled at 50-70 wt %; (2) Next, the obtained casting solution is coated on a glass plate by knife coating, pre-evaporated at room temperature for 5-300 seconds, and then immersed in one or more mixed non-solvents at -25-30°C for 5-30 minutes for conversion, condensation, film formation and washing to remove the solvent, thereby achieving phase inversion; (3) Soaking the membrane obtained in the above step in deionized water at 50-100° C. for 24-48 hours to remove the residual solvent in the membrane, and finally preparing a polysulfone-ZrO2 composite membrane material.

5. The method according to claim 4, characterized in that: The organic solvent described in step (1) is N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), N,N'-dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or tetramethyl urea (TMU).

6. The method according to claim 4, characterized in that: The non-solvent described in step (2) is: one or a mixed solvent of two or more of water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol and tert-butanol.

7. Use of the polysulfone-ZrO2 composite membrane material according to any one of claims 1 to 3 or the polysulfone-ZrO2 composite membrane material prepared by the method according to any one of claims 4 to 6 in an alkaline water electrolysis device, characterized in that: The steps include: (1) Preparation of membrane electrode assembly for alkaline water electrolysis device Pure nickel mesh foam is used for both cathode and anode, and the pure nickel mesh foam is placed in a hot press, hot-pressed at 80-120°C for 0.5-10 minutes, then taken out and compressed to a thickness of 150-200 μm, and then a polysulfone-ZrO2 composite membrane material is sandwiched between two nickel mesh foam electrodes to obtain a membrane electrode assembly; (2) Assemble the alkaline water electrolysis device by sandwiching the membrane electrode assembly between the cathode and the anode Electrochemical tests were performed in the presence of anodic and cathodic electrolytes. Polarization curves were obtained by measuring the cell voltage at different current densities in 1-10 M electrolytes at 20-100 °C, and at 20-100 °C, 50-500 mA cm -2 The durability is evaluated under constant temperature and constant current conditions.

8. The use according to claim 7, characterized in that: The electrolyte in the alkaline water electrolysis device is one or more of potassium hydroxide, potassium carbonate, potassium bicarbonate, sodium hydroxide, sodium carbonate and sodium bicarbonate.

Citation Information

Patent Citations

  • Integrated membrane electrode and preparation method and application thereof

    CN112144076A

  • Composite diaphragm, preparation method thereof and secondary battery

    CN113851787A